Biosecurity hygiene in the Australian high country: footwear cleaning practices, motivations, and barriers among visitors to Kosciuszko National park. Issue 4 (1st October 2020) - Gill, Nicholas; McKiernan, Shaun; Lewis, Anna; Cherry, Hillary; Annunciato, Drauzio
ABSTRACT: Conservation areas face growing visitor numbers and heightened biosecurity risks from vectors such as bushwalkers and mountain bikers. For mountain areas, such pressures, with climate change, may be increasing in vulnerability to invasive species. Strategies to manage these risks include encouraging visitors to undertake biosecurity hygiene practices such as cleaning footwear at trailhead cleaning stations. However, limited social science biosecurity hygiene research has been undertaken. We address the issue by using a survey based on a social marketing approach to assess footwear cleaning practices among walkers in Kosciuszko National Park in south-eastern Australia. We identified perceived barriers and benefits to footwear cleaning among walkers, finding a low level of cleaning but that most walkers identified addressing biosecurity risks as a benefit from cleaning. Barriers to cleaning included queues and station maintenance. We use elements from the Theory of Planned Behaviour as a heuristic to reflect on walker behaviour and responses. Outcomes suggest strategies for station installation and design, and the value of further research into visitor norms and behaviour. We reflect on the use of social marketing and what it asks of both visitors and managers.